Lifestyle counselling as secondary prevention in patients with minor stroke and transient ischemic attack: study protocol for a randomized controlled pilot study - Liljehult, Jacob (Pilot Feasibility Stud, 2020)
BACKGROUND: Most patients with minor stroke or transient ischemic attack (TIA) are discharged with little or no specialised follow-up. Nonetheless, these patients have a high prevalence of cognitive impairments and a considerable risk of recurrent stroke. Smoking cessation, physical activity, and adherence to antihypertensive and antithrombotic medication are highly recommended in patients with minor stroke and TIA. Evidence suggests that simple encouragement to change lifestyle is ineffective. Behavioural interventions might therefore be needed to support patients in managing their own health post-discharge. OBJECTIVES: We aim to test the (1) feasibility of randomisation acceptance and an early initiated, client-centred lifestyle and behavioural intervention in a clinical setting, and (2) potential effect of the intervention on arterial blood pressure in patients with minor stroke or TIA and (3) explore the participants experience of barriers and facilitators for health behaviour after a stroke, including perceived needs and social support. METHODS: We will conduct a randomized controlled pilot trial: Eligible patients with acute minor stroke or TIA (n = 40) will be randomly allocated to either early initiated counselling with four weekly post-discharge follow-up sessions for 12 weeks or usual care. The primary outcome will be program feasibility and to discuss the relevance of arterial blood pressure as primary outcome after 12 weeks intervention. Selected participants will be invited to participate in semi-structured interviews, based on purposeful sampling, to evaluate the intervention and explore their experience of life after a stroke. The interviews will be analysed using a five-step thematic analysis approach. DISCUSSION: The study will provide evidence of the feasibility and potential effect of early initiated counselling on cardiovascular risk factors in patients with minor stroke and TIA. Qualitative interviews will contribute with a more nuanced understanding of the barriers and facilitators of health enhancing behaviour. Optimizing health behaviour counselling and providing formal support to the patients’ post-discharge may ease the transition and help more patients adhere to lifestyle and medication recommendations. TRIAL REGISTRATION: ClinicalTrial.gov, NCT03648957